Attenuated secretion of glucose-dependent insulinotropic polypeptide (GIP) does not alleviate hyperphagic obesity and insulin resistance in ob/ob mice - Satoko Shimazu-Kuwahara; Norio Harada; Shunsuke Yamane; Erina Joo; Akiko Sankoda; Timothy J. Kieffer; Nobuya Inagaki (Elsevier, 2017)
Objective: Glucose-dependent insulinotropic polypeptide (GIP) is released during meals and promotes nutrient uptake and storage. GIP receptor knockout mice are protected from diet induced weight gain and thus GIP antagonists have been proposed as a treatment for obesity. In this study, we assessed the role of GIP in hyperphagia induced obesity and metabolic abnormalities in leptin deficient (Lepob/ob) mice. Methods: We crossbred GIP-GFP knock-in homozygous mice (GIPgfp/gfp) that have complete GIP knockout, and mice heterozygous for the ob mutation (Lepob/+) mice to generate Lepob/+/GIP+/+, Lepob/ob/GIP+/+, and Lepob/ob/GIPgfp/gfp mice. Male animals were weighed weekly and both oral glucose and insulin tolerance testing were performed to assess glucose homeostasis and circulating profiles of GIP and insulin. Body composition was evaluated by computerized tomography (CT) scan and analyses of indirect calorimetry and locomotor activity were performed. Results: Postprandial GIP levels were markedly elevated in Lepob/ob/GIP+/+ mice compared to Lepob/+/GIP+/+ controls and were undetectable in Lepob/ob/GIPgfp/gfp mice. Insulin levels were equivalently elevated in both Lepob/ob/GIP+/+ and Lepob/ob/GIPgfp/gfp mice compared to controls at 8 weeks of age but the hyperinsulinemia was marginally reduced in Lepob/ob/GIPgfp/gfp by 21 weeks, in association with amelioration of glucose intolerance. Both Lepob/ob/GIP+/+ and Lepob/ob/GIPgfp/gfp mice remained equivalently insulin resistant. Body weight gain and subcutaneous and visceral fat volume of both Lepob/ob/GIP+/+ and Lepob/ob/GIPgfp/gfp mice were significantly higher than that of Lepob/+/GIP+/+ mice, while no significant differences were seen between Lepob/ob/GIP+/+ and Lepob/ob/GIPgfp/gfp mice. Locomotor activity and energy expenditure were decreased in both Lepob/ob/GIP+/+ and Lepob/ob/GIPgfp/gfp mice compared to control Lepob/+/GIP+/+ mice, while no significant differences were seen between Lepob/ob/GIP+/+ and Lepob/ob/GIPgfp/gfp mice. There was no significant difference in fat oxidation among the three groups. Fat content in liver was significantly lower in Lepob/ob/GIPgfp/gfp compared to Lepob/ob/GIP+/+ mice, while that of control Lepob/+/GIP+/+ mice was the lowest. Conclusions: Our results indicate that GIP knockout does not prevent excess weight gain and metabolic derangement in hyperphagic leptin deficient mice. Keywords: GIP, Hyperphagia, Obesity, Insulin resistance, ob/ob